2018
DOI: 10.1103/physrevlett.121.026808
|View full text |Cite
|
Sign up to set email alerts
|

Biorthogonal Bulk-Boundary Correspondence in Non-Hermitian Systems

Abstract: Non-Hermitian systems exhibit striking exceptions from the paradigmatic bulk-boundary correspondence, including the failure of bulk Bloch band invariants in predicting boundary states and the (dis)appearance of boundary states at parameter values far from those corresponding to gap closings in periodic systems without boundaries. Here, we provide a comprehensive framework to unravel this disparity based on the notion of biorthogonal quantum mechanics: While the properties of the left and right eigenstates corr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
928
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,196 publications
(950 citation statements)
references
References 45 publications
19
928
2
1
Order By: Relevance
“…Hence, the feedback control interactions define distinct phases characterized by winding numbers which exhibit opposite behaviors for lattices with γ c = 0.1 and γ c = −0.1. These behaviors manifest as localized bulk Eigen modes in finite lattices, a phenomenon known as non-Hermitian skin-effect (NHSE) [65][66][67][68][69][70][71]. As an illustration, the Eigen frequencies of a finite lattice with N = 100 masses under free-free boundary conditions are displayed as black dots in figures 4(b) and (h), while representative Eigen modes marked by the blue circles are displayed in figures 4(c) and (i).…”
Section: Bulk Topology and Non-hermitian Skin Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the feedback control interactions define distinct phases characterized by winding numbers which exhibit opposite behaviors for lattices with γ c = 0.1 and γ c = −0.1. These behaviors manifest as localized bulk Eigen modes in finite lattices, a phenomenon known as non-Hermitian skin-effect (NHSE) [65][66][67][68][69][70][71]. As an illustration, the Eigen frequencies of a finite lattice with N = 100 masses under free-free boundary conditions are displayed as black dots in figures 4(b) and (h), while representative Eigen modes marked by the blue circles are displayed in figures 4(c) and (i).…”
Section: Bulk Topology and Non-hermitian Skin Effectmentioning
confidence: 99%
“…Further observations of a seemingly breakdown of the bulk-boundary correspondence principle [62,63] has led to proposals for a general classification of the topological phases of non-Hermitian systems [55,56,64]. A particular point of interest is the observation of the non-Hermitian skin effect [65][66][67][68][69][70][71], whereby all Eigen states of one-dimensional (1D) systems are localized at a boundary, in sharp contrast with the extend Bloch modes of Hermitian counterparts. This intriguing feature of non-Hermitian lattices has recently been experimentally demonstrated using topo electrical circuits [72] and quantum walks of single photons [73].…”
Section: Introductionmentioning
confidence: 99%
“…invariants based on a finite system rather than bulk states, or invariants defined in real space [127]. A similar approach, without reference to Bloch states but rather a system with open boundaries, was presented by Kunst and collaborators [59].…”
Section: The Many Paths To a Bulk-boundary Correspondencementioning
confidence: 99%
“…On the other hand, there is an intense activity in the search for a consistent classification [51][52][53][54][55], the definition of the topological invariants [56][57][58], and the search for a bulk-boundary correspondence [47,48,59,60].…”
Section: Introductionmentioning
confidence: 99%
“…Topological phases and topological phase transitions in fermionic and bosonic systems, described by Hermitian Hamiltonians, have attracted great interests in past three decades [1][2][3]. Recent studies have revealed that topological phases can be extended to non-Hermitian systems beyond the scope of closed systems [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Especially, the interplay between non-Hermiticity and topological states leads to unique properties that have no counterparts in Hermitian systems [20,21].…”
Section: Introductionmentioning
confidence: 99%